IMPLEMENTASI GAP (GOOD AGRICULTURAL PRACTICES) PADA PETANI HORTIKULTURA DAN STRATEGI PENGEMBANGANNYA DI KABUPATEN PAMEKASAN - Lia Kristiana; Moh. Shoimus Sholeh (University of Jember, 2020)
Farmers need to apply GAP To produce a sustainable production system, the products produced are of good quality, can be accepted by markets, the products have competitiveness. This study aims to 1). Determine the application of GAP in horticultural farmers in Pamekasan 2). Know the GAP Development Strategy in Horticulture in Pamekasan Regency. The analysis used is a SWOT analysis. To identify external and internal factors of farmers in the application of horticultural GAP which consists of strengths, weaknesses, threats, and opportunities that exist. The results showed that 100% of Horticultural Farmers in Pamekasan Regency in managing human resources were not in accordance with GAP standards, 100% of farmers in farming were not in accordance with GAP. That is because currently the implementation of horticultural farming is only based on the standard operational procedure (SOP) of the planted variety. Strategy of Farmers in the development of horticultural GAP in Pamekasan Regency, namely through the SO strategy (enhancing guidance to farmers through training and demonstration plots) on horticultural GAP to horticultural farmers), ST (submitting application to the agriculture department related to the implementation of horticultural GAP training), WO (enhancing Farmers' knowledge and skills by including competency testing farmers), WT (Increasing interaction with BBPP and local tertiary institutions in implementing Horticultural GAP). Keywords: Strategy, Good Agricultural Practices, SWOT.